CRYPTOGENIC MULTIFOCAL ULCEROUS STENOSING ENTERITIS (CMUSE): A 20-YEAR SINGLE CENTER CLINICAL AND RADIOLOGIC EXPERIENCE. (21st January 2021) - Ramos, Guilherme Piovezani; Bartlett, David; Bledsoe, Adam; Bruining, David; Fidler, Jeff; Sheedy, Shannon; Murray, Joseph
Abstract: Background: Cryptogenic multifocal ulcerous stenosing enteritis (CMUSE) is a rare illness characterized by multiple strictures and shallow ulcers of the small bowel. Even though diagnostic criteria have been described, further ellucidation is needed on therapeutic interventions and potential discriminating factors between CMUSE and other more common causes of intestinal ulcerations, including Crohn's disease. Aim: The purpose of this article is to report the clinical, CT, and MR enterography characteristics of confirmed cases of CMUSE. Materials and Methods: Retrospective review of electronic medical records identified 33 patients considered for a diagnosis CMUSE. Diagnosis was confirmed if all requirements of the previously published diagnostic criteria for CMUSE were met. Patients were excluded if they had less than one year follow-up or incomplete clinical data. Two GI radiologists reviewed all CT and MR enterography (CTE/MRE) exams in consensus of confirmed patients to characterize the cross sectional imaging features. Results: CMUSE was confirmed in 9 patients (27%) and 24 patients (73%) had a confirmed alternative diagnosis. Crohn's disease (CD) (30%, n=7) and drug-induced enteropathy (30%, n=7) were the most frequent alternative. Male gender (66.7% vs. 25%, p=0.04) and clinical manifestation of anemia at presentation were more commonly observed on CMUSE-confirmed cases (66.7% vs. 4.2%, p=0.005) when compared to patients with non-CMUSE diagnosis, in which abdominal pain was the most common presenting symptom (44.5% vs 87.5%, p=0.02). Multiple (100%) and circumferential (75%) ulcers with restricted mucosal involvement (55.6%) were major features at endoscopy and pathology. Most common treatments were corticosteroids (78%) or surgical resection (55.6%), with 33% receiving biologics. Disease recurrence after first treatment occurred in the majority (88.9%) after a median time of 6 months (Table 1). 9 CTE and 1 MRE of 8 confirmed cases images were analyzed (Table 2). Major imaging features included multiple (≥ 5; 88%; 7/8), short (< 2 cm; 100%; 8/8) circumferential (100%;8/8) strictures with moderate wall thickening (6–9 cm), and stratified hyper enhancement (100%; 8/8) located in the ileum (100%; 8/8). Median proximal small bowel dilation was 2.95 cm (2.5–4.1 cm). Less common findings included: mesenteric adenopathy (50%; 4/8), increased mesenteric edema/ascites (38%; 3/8), mesenteric vascularity (25%; 2/8), colon inflammation (13%; 1/8), and decreased small bowel fold pattern (13%; 1/8). No patients with confirmed CMUSE cases demonstrated penetrating disease (e.g., abscess, fistula). Conclusion: CMUSE is rare cause of small bowel strictures with overlapping clinical and imaging features of more common etiologies such as Crohn's Disease and NSAID enteropathy that need to be excluded through a multidisciplinary approach to confirm the diagnosis.